Speech Behavior and the Formation of a Multicultural Linguistic Personality in the Context of Acmeology - M.Sh. Makhamedova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
this article explores the role of speech behavior as a fundamental mechanism for an individual’s attainment of "acme" – the peak of professional and personal development. Integrating perspectives from acmeology, sociolinguistics, and pragmatics, the study examines speech behavior as a multifaceted phenomenon shaped by social structures, geographical contexts, and individual characteristics. The author highlights the acmeological approach to developing communicative competence, which encompasses not only linguistic mastery but also emotional self-regulation and strategic adaptability. In the context of modern globalization, the article analyzes the dialectical tension between cultural unification and the intensification of national self-identification. A central focus is placed on the formation of a "multicultural linguistic personality" equipped with poly-conceptual competence. Drawing on the specific linguistic landscape of the Republic of Uzbekistan, the paper demonstrates how state strategies in language regulation and multi-ethnic education foster a constructive environment for intercultural dialogue. The study concludes that the development of a multicultural linguistic personality is a prerequisite for achieving professional excellence and social harmony in the contemporary globalized world.